Critical Reflection in Peer Feedback: Assessing the Evaluative Quality of Peer Comments in Collaborative Writing Tasks - Arif Putra Yogesi; La Sunra; Muh. Tahir (Universitas Islam Negeri Palopo, 2026)
Peer feedback is an integral part of collaborative writing; nevertheless, the evaluative depth of student comments is often limited. This study examines the quality of peer feedback among 15 participants in a mixed-age English language course where age differences and social hierarchy may influence evaluative interaction. This research employs Qualitative Content Analysis (QCA) and centers around two primary questions: to what extent do student peer comments reflect critical engagement versus technical corrections (RQ1), and what are the common patterns of evaluative reasoning (RQ2). Data were collected via a Peer Feedback Worksheet designed and assessed by an evaluation rubric, from Level 1 (Corrective) to Level 3 (Strategic). The results reveal that roughly 60% of student comments were superficial, largely addressing minor technical issues such as spelling and grammar. Qualitative patterns imply that social dynamics, notably age seniority and a need for social civility, greatly inhibit students from giving strategic, high-quality comments. The younger participants were uncomfortable evaluating their older peers, resulting in a “safety-first” approach to their reasoning. The study suggests that language proficiency is not sufficient for effective peer feedback and that educational interventions should target social-emotional feedback literacy to enhance deeper critical reflection in different EFL settings. The study also highlights the importance of social-emotional feedback literacy in improving peer-feedback pedagogy in EFL contexts.